Hukum Musyarakah Mutanaqhisah dan Implementasinya pada Perbankan Syariah - Slamet Akhmadi (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2019)
House is part of everyobe needs. In oder to get house they deired, they can use Islamic Banking services. One of financial products offered by Islamic Banks is financing home ownership or conventional banks loans reffered to as products (Mortgages). In offering products related to home ownership, islamic banking is using Musharaka Mutanaqisha contract (Transaction). The purpose of this paper is to determine the extent of Mutanaqishah Musyarakah law and its implementation in Islamic bank institutions. The result of this study shows that this type of contract (musyarakah mutanaqishah) is legal and can be implemented in Islamic bank institutions in financing products for the procurement of goods (houses)